Juridical Analysis of Unlawful Acts at the Indonesian Exim LPEI Bank: Analysis of Decision No. 42/PDT/2025/PT MDN of the Medan High Court - Nasution, Emmi Rahmiwita (Westscience Press, 2025)
This study explores the issue of unlawful acts (perbuatan melawan hukum) within the Indonesian Export-Import Bank (LPEI), focusing on the analysis of Decision No. 42/PDT/2025/PT MDN issued by the Medan High Court. Utilizing a normative juridical approach, the research examines the legal principles underlying the court's judgment, including breaches of fiduciary duties, negligence in risk management, and the application of Articles 1365 and 1366 of the Indonesian Civil Code. The findings reveal significant governance lapses within LPEI, leading to financial losses and diminished accountability. The study highlights the need for strengthened internal controls, enhanced risk management systems, and regulatory reforms to improve the governance of state-owned enterprises. This analysis contributes to the understanding of legal accountability in financial institutions and offers recommendations for preventing similar cases in the future.